PARADOKS PERUBAHAN SOSIAL BALI DALAM CERPEN INDONESIA DAN BALI MODERN - Sujaya, I Made; Adhi Dwipayana, I Kadek; Liswahyuningsih, Ni Luh Gede (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2024)
This article discusses the representation of Balinese social change in modern Indonesian and Balinese short stories. The objects of study are the Indonesian short story, "Paradoks" by Putu Wijaya and the Balinese short story, "Jaen Idup di Bali" by Made Suar-Timuhun. The main problem in this study is how social change in Bali and the response of the Balinese people represented in these two short stories. By using semiotics theory, especially Algirdas J. Greimas' isotopic analysis model, this study finds that the two short stories represent a paradox in Balinese social change. The Balinese characters in the short story are described as viewing Balinese social change with anxiety, whereas people from outside Bali see Balinese social change as a gift that must be grateful for. This paradoxical picture reflects the social reality in Balinese society today in facing social changes in its homeland.